TAT-Gap19 and Carbenoxolone alleviate liver fibrosis in mice - Yanguas, Sara Crespo; da Silva, Tereza C.; Pereira, Isabel V. A.; Willebrords, Joost; Maes, Michaël; Nogueira, Marina Sayuri; de Castro, Inar Alves; Leclercq, Isabelle; Romualdo, Guilherme R. [UNESP]; Barbisan, Luís F. [UNESP]; Leybaert, Luc; Cogliati, Bruno; et al. (MDPI, 2018)
Although a plethora of signaling pathways are known to drive the activation of hepatic stellate cells in liver fibrosis, the involvement of connexin-based communication in this process remains elusive. Connexin43 expression is enhanced in activated hepatic stellate cells and constitutes the molecular building stone of hemichannels and gap junctions. While gap junctions support intercellular communication, and hence the maintenance of liver homeostasis, hemichannels provide a circuit for extracellular communication and are typically opened by pathological stimuli, such as oxidative stress and inflammation. The present study was set up to investigate the effects of inhibition of connexin43-based hemichannels and gap junctions on liver fibrosis in mice. Liver fibrosis was induced by administration of thioacetamide to Balb/c mice for eight weeks. Thereafter, mice were treated for two weeks with TAT-Gap19, a specific connexin43 hemichannel inhibitor, or carbenoxolone, a general hemichannel and gap junction inhibitor. Subsequently, histopathological analysis was performed and markers of hepatic damage and functionality, oxidative stress, hepatic stellate cell activation and inflammation were evaluated. Connexin43 hemichannel specificity of TAT-Gap19 was confirmed in vitro by fluorescence recovery after photobleaching analysis and the measurement of extracellular release of adenosine-5′-triphosphate. Upon administration to animals, both TAT-Gap19 and carbenoxolone lowered the degree of liver fibrosis accompanied by superoxide dismutase overactivation and reduced production of inflammatory proteins, respectively. These results support a role of connexin-based signaling in the resolution of liver fibrosis, and simultaneously demonstrate the therapeutic potential of TAT-Gap19 and carbenoxolone in the treatment of this type of chronic liver disease.
Keywords: Connexin43; Gap junction; Hemichannel; Hepatic stellate cells; Inflammation; Liver fibrosis